An Integrated Model‐Based Approach to System Safety and Aircraft System Architecture Development. Issue 1 (28th October 2015) - Villhauer, Eric; Jenkins, Brian
Abstract: Industry standards for aircraft development require consideration of System Safety objectives during all phases of System Architecture development and implementation. However, tools that have enabled Systems Engineers and Software Engineers to create high‐fidelity models of System Architectures currently don't address the concerns of the System Safety Engineering discipline. A strategy is necessary to ensure that safety objectives are considered during System Architecture model development while maintaining the required organizational independence between System Safety and the domains with which they interface. This paper details an approach to include a view in an architectural model that addresses System Safety objectives.